نحو سياسة ضريبية داعمة للاستثمار في المؤسسات الصغيرة والمتوسطة: Towards a tax policy supportive of investment in small and medium enterprises. - زواق الحواس (Journal of North African Economies, 2025)
The study aimed to try to present a vision of the main features of the tax policy that could contribute to stimulating investment in small and medium enterprises to serve the general objectives of the state's economic policy, as facts confirm from day to day that these projects are the most capable of leading economies towards development. Therefore, the study touched on the economic literature of tax policy, and then presented a perception about the mechanisms of employing this policy to attract small and medium investments. The study concluded that the tax policy has the tools and options that guarantee positive effects on the investments of small and medium enterprises, if it is formulated through tax legislation commensurate with the peculiarities of these institutions, based on simplicity and transparency of procedures, rational rates, effectiveness in the face of tax evasion and double taxation, Contribute to removing obstacles to these institutions;